(untitled) (Research, Society and Development, 2022)
The importance of adopting technology innovations, mainly in food production contributing to food safety, is significant. This study aims to analyze the diffusion of agricultural production technologies in Brazil, mainly the use of wheel tractors, grain and sugarcane harvesters by producers. A quantitative approach is used to understand the market-level factors that influence the adoption of technologies. A supply response is estimated based on the Bass diffusion model. Data were collected from the National Association of Vehicle Manufacturers (Anfavea), which includes Brazilian monthly sales information for wheel tractors, grain and sugarcane harvesters. For each agricultural machine, 700 months of sales records were collected. The imitator’s coefficients were higher than innovators for all types of machines studied. The data showed that, for wheel tractors and grain harvesters, the diffusion curve presented S format (S-curves). However, sugarcane harvesters had a different pattern of diffusion. The distribution of the investigated technologies in Brazil was an imitation process; the market saturation was observed for wheel tractors and grain harvesters. This study helps to comprehend the supply response of agricultural machinery and presents suggestions for the diffusion of agricultural production technologies in Brazil. The experience has shown that several factors can constrain technology adoption, such as lack of credit, limited access to information and inputs, and inadequate infrastructure.